Immunomodulatory effects of Companilactobacillus allii WiKim39 and Lactococcus lactis WiKim0124 isolated from kimchi on lipopolysaccharide-induced RAW264.7 cells and dextran sulfate sodium-induced colitis in mice. (March 2022) - Yun, Ye-Rang; Lee, Moeun; Song, Jung Hee; Choi, Eun Ji; Chang, Ji Yoon
Graphical abstract: Highlights: Vegetable juice was fermented with Companilactobacillus allii WiKim39 or Lactococcus lactis Wikim0124 isolated from kimchi. VJ + WiKim39 and VJ + WiKim0124 exhibited anti-inflammatory effects in LPS-induced RAW264.7 cells. VJ + WiKim39 and VJ + WiKim0124 exhibited anti-inflammatory effects in DSS-induced colitis in mice. The anti-inflammatory effects of VJ + WiKim39 and VJ + WiKim0124 were established via the NF-kB pathway in vitro and in vivo . Abstract: Lactic acid bacteria (LAB) isolated from kimchi has beneficial antioxidant, anti-obesity, anti-cancer and immunomodulatory effects. Here, we investigated the immunomodulatory effects of vegetable juice (VJ) fermented with Companilactobacillus allii WiKim39 (VJ + WiKim39) or Lactococcus lactis WiKim0124 (VJ + WiKim0124) isolated from kimchi, in vitro and in vivo . Nitric oxide (NO) production and levels of inflammatory markers were significantly lower in lipopolysaccharide (LPS)-stimulated RAW264.7 cells treated with heat-inactivated VJ + WiKim39 and heat-inactivated VJ + WiKim0124 than in untreated cells ( P  < 0.05). In mice with dextran sulfate sodium (DSS)-induced colitis, oral administration of VJ + WiKim39 and VJ + WiKim0124 attenuated DSS-induced decrease in colon length and mucosal epithelia. Moreover, VJ + WiKim39 and VJ + WiKim0124 significantly downregulated several inflammatory markers ( P  < 0.05). Overall, WiKim39 and WiKim0124 showed immunomodulatory activity in vitro and in vivo and thus, they could be used in health promoting fermented foods.